Contribution of Work Experience and Career Development to Increase Employee Productivity of Telecommunication Companies - Narpati, Bintang; Dharmanto, Agus; Supardi; Jumawan (Draf Solusi Indonesia, 2025)
A B S T R A C T This study aims to analyze the influence of career development and work experience on employee work productivity. The research is quantitative with an explanatory research approach. The study population was all employees of the company and a sample of 100 respondents was determined using the Slovin formula with an error rate of 5%. Data collection was carried out through a questionnaire with a 5-point Likert scale. The independent variables consist of Work Experience (X1) and Career Development (X2), while the dependent variable is work productivity (Y). Data analysis used multiple linear regression with the help of SPSS software version 27. The results of the validity test show all valid statement items. The reliability test resulted in a Cronbach's Alpha value of > 0.70 so it was reliable. The normality test with Kolmogorov-Smirnov showed normally distributed data on all three variables (Asymp. Sig. > 0.05). A partial t-test showed that work experience had a significant effect on work productivity and career development with an Adjusted R Square value of 0.260 or 26%, meaning that 26% of the variation in work productivity could be explained by work experience and career development, while the remaining 74% were influenced by other variables outside the model. The conclusion of this study is that both work experience and career development partially have a positive and significant effect on employee work productivity. The breadth of the employee's work experience and the better, the career development program (promotion, training, job rotation), the higher the level of work productivity that can be achieved. Therefore, companies are advised to continue to improve structured and equitable career development programs and utilize experienced employees as mentors or coaches for junior employees to support continuous productivity improvement.